Foraging Activities of Apis Cerana in a Coconut Plantation - Abdullah, Mai Shihah (1990)
Honey production of Apis cerdna has been limited for a long time by outdated management methods and the lack of knowledge of bee behaviour. A great variety of plants are found in Malaysia and many flower throughout the year. Particularly important in bee keep ingare the two major nectar flow periods that occurin February and August-September. This study is based on observation of foraging by three colonies of Apis ceranaina coconut plantationat Tanjung Karang, Selangor Darul Ehsan, Peninsular Malaysia from March 1988 until March 1989. The major nectar sources were coconut, Cocosnucifera (Palmae) and the weed, Asystasia intrusa (Acanthaceae). While A. intrusa flowers throughout the year, coconut shows marked peaks of f lowering from February to June and August to September with a dearth period in December to January